SUCCESS OF PERCUTANEOUS NEPHROLITHOTOMY: COMPARING SPINAL ANESTHESIA WITH GENERAL ANESTHESIA - Astram, Ari; Birowo, Ponco; Rasyid, Nur; Pryambodho, P; Susilo, C (Indonesian Journal of Urology, 2015)
Objective: The purpose of this study compared the outcome of PCNL under general and spinal anesthesia for the outcome. Material & Methods: PCNL had been performed from 2000 until 2011 with total 760 PCNL divided into 220 PCNL using general anesthesia (Group A) and the remaining 540 PCNL using spinal anesthesia (Group B) The data of both groups were evaluated with Chi square test, and Mann-Whitney test. Result: Stone free rate in Group A was 71.37% similar with Group B 72.97% (p > 0.05). Spinal anesthesia was used more often in patient who had previous surgery 65.5% compared with general anesthesia 36.82% (p < 0.05). The average surgery duration in Group A was longer than group B (77.10 ± 35.59 minutes vs 68.42 ± 30.55 minutes) (p < 0.05). The average length of hospital stay in Group B was shorter than Group A (3.90 ± 2.72 days vs 5.47 ± 4.25 days) (p < 0.05). There was no difference between Group A and Group B in complication and the needs of tranfusion. Conclusion: PCNL under spinal anesthsia was feasible and safe even better in the shorter surgery duration and the length of hospital stay.